Trend of pregnancy outcomes in type 1 diabetes compared to control women: a register-based analysis in 1996-2018 - Fazekas-Pongor, Vince; Svébis, Mark M.; Major, David; Pártos, Katalin; Dósa, Norbert; Mészáros, Ágota; Horváth, Viktor J.; Domján, Beatrix A.; Zsirai, László; Tabák, Adam G. (Frontiers in Endocrinology, 2023)
In 1989, the St Vincent declaration aimed to approximate pregnancy outcomes of diabetes to that of healthy pregnancies. We aimed to compare frequency and trends of outcomes of pregnancies affected by type 1 diabetes and controls in 1996-2018.We used anonymized records of a mandatory nation-wide registry of all deliveries between gestational weeks 24 and 42 in Hungary. We included all singleton births (4,091 type 1 diabetes, 1,879,183 controls) between 1996 and 2018. We compared frequency and trends of pregnancy outcomes between type 1 diabetes and control pregnancies using hierarchical Poisson regression.The frequency of stillbirth, perinatal mortality, large for gestational age, caesarean section, admission to neonatal intensive care unit (NICU), and low Appearance, Pulse, Grimace, Activity, and Respiration (APGAR) score was 2-4 times higher in type 1 diabetes compared to controls, while the risk of congenital malformations was increased by 51% and SGA was decreased by 42% (all p<0.05). These observations remained significant after adjustment for confounders except for low APGAR scores. We found decreasing rate ratios comparing cases and controls over time for caesarean sections, low APGAR scores (p<0.05), and for NICU admissions (p=0.052) in adjusted models. The difference between cases and controls became non-significant after 2009. No linear trends were observed for the other outcomes.Conclusions: Although we found that the rates of SGA, NICU care, and low APGAR score improved in pregnancies complicated by type 1 diabetes, the target of the St Vincent Declaration was only achieved for the occurrence of low APGAR scores.